Analisis Konsekuensi Hukum Keanggotaan Indonesia dalam Perjanjian World Trade Organization - Intan Pelangi (KEADILAN PROGRESIF, 2017)
Indonesia as a developing country is also a member of International Organization, such as WTO (World Trade Organization), APEC (Asia Pacific Economic Cooperation), and FTA (Free Trade Area) which has the nuance of free trade. The problem in this research is how the legal consequences for Indonesia in WTO agreement. The problem approach in this research is the normative juridical approach that is approach by reviewing the rules related to the problem to be discussed. After data is collected and processed, then analyzed qualitatively. The results of this study indicate that Indonesia is legally bound by the terms of the WTO Agreement. For Indonesia, which does not embrace one theory in absolute terms, either incorporation or transformation, then there are two consequences juridically, ie externally and internally.